Detection of multiple terrestrial gamma‐ray flashes from thunderstorm systems. Issue 11 (9th November 2016) - Ursi, A.; Marisaldi, M.; Tavani, M.; Casella, D.; Sanò, P.; Dietrich, S.
Abstract: Since their discovery, Terrestrial Gamma ray Flashes (TGFs) exhibited an evident correlation with thunderstorms and lightning activity. The fleeting nature of these events and the heavy absorption of gamma rays in the lowest atmospheric layers severely hamper the observation of this phenomenon, making us reveal just a small fraction of a probably much wider population. As each thunderstorm produces a large amount of lightning discharges during its lifetime, it is reasonable that even a large amount of TGFs are produced during the same event. However, detection of multiple TGFs coming from the same storm is difficult to perform, as it requires the constant monitoring of a spatially limited geographic region: this is not an easy task to perform for satellites on high‐inclination orbits that make them experience nonnegligible latitudinal shifts at each orbital passage over a certain region, preventing the monitoring of a limited geographic region throughout successive overpasses. In this perspective, the quasi‐equatorial (2.5°) orbit of the Astrorivelatore Gamma ad Immagini LEggero (AGILE) satellite ensures a minimal latitudinal shift when flying over the same region at successive passages, allowing for the follow‐up of thunderstorms in time. We exploit this feature of the AGILE satellite to search for multiple TGFs coming from the same geographic region and, in particular, from the same thunderstorm. We carry out this search on the AGILE TGF database (2009–2016), ending up with a sample of 79 systems producing more than one TGF, both during the same overpass and up to four overpasses after. Data acquired by geostationary meteorological satellites and cross correlation with radio sferics detected by World Wide Lightning Location Network are used to support this investigation. The AGILE satellite for the first time clearly establishes the multiple occurrences of TGFs from convective thunderstorms, both on timescales of minutes to several hours. Key Points: The AGILE satellite observed more TGFs originating from the same spatially limited geographic regions This work represents an indirect evidence that more TGFs can be produced by thunderstorms throughout their lifetime The orbit of the AGILE satellite is unique to perform follow‐up of thunderstorms in time